Exploration of the arthropod virome, its biological impacts on host health, and its potential implementation in biocontrol - Cross, Shaun T., author; Stenglein, Mark D., advisor; Wilusz, Jeffrey, committee member; Foy, Brian D., committee member; Metcalf, Jessica L., committee member (Colorado State University. Libraries, 2020)
With the advent of next generation sequencing, viruses are being discovered at an unprecedented rate. The collection of these viruses, known as the virome, and their impact on the host is relatively understudied compared to the bacterial microbiome. The underlying goal of this thesis work was to better understand how the virome interacts with the host, and this has been accomplished in two ways. First, we biologically characterized predominant virus constituents in arthropod viromes, namely arthropod-infecting partitiviruses. In a subsequent study we measured how one of these partitiviruses, galbut virus, impacted the fitness of Drosophila melanogaster. Second, we searched for evidence that these viruses are active in their interactions with fellow microbial constituents within the host. Specifically, we addressed how the virome may change disease vectors' competence in harboring and transmitting pathogens with a focus on Ixodes scapularis ticks. Partitiviruses are segmented, multipartite dsRNA viruses that until recently were only known to infect fungi, plants, and protozoans. Metagenomic surveys have revealed that partitivirus-like sequences are also commonly associated with arthropods. One arthropod-associated partitivirus, galbut virus, is common in wild populations of D. melanogaster. To begin to understand the processes that underlie this virus's high global prevalence, we established colonies of wild-caught infected flies. Infection remained at stably high levels over three years, with between 63-100% of individual flies infected. Galbut virus infects fly cells and replicates in tissues throughout infected adults, including reproductive tissues and the gut epithelium. We detected no evidence of horizontal transmission via ingestion but vertical transmission from either infected females or infected males was ~100% efficient. Vertical transmission of a related partitivirus, verdadero virus, that we discovered in a laboratory colony of Aedes aegypti mosquitoes was similarly efficient. This suggests that efficient biparental vertical transmission may be a feature of at least a subset of insect-infecting partitiviruses. To study the impact of galbut virus infection free from the confounding effect of other viruses, we generated an inbred line of flies with galbut virus as the only detectable virus infection. We were able to transmit the infection experimentally via microinjection of homogenate from these galbut-only flies. This sets the stage for experiments to understand the biological impact and possible utility of partitiviruses infecting model organisms and disease vectors. Using the galbut virus and D. melanogaster system, we set forth to answer: what are the biological effects, if any, of galbut virus infection on D. melanogaster fitness? Using multiple lines of flies from the Drosophila Genetic Reference Panel (DGRP) that differed only in their galbut virus infection status, a variety of fitness measurements were performed across both sexes. Galbut virus minimally impacted lifespan and had no effects on fecundity, but infection did significantly impact developmental speeds of flies. When challenged with various viral, bacterial, and fungal pathogens, some galbut virus infected flies had altered sensitivity to these pathogens. These susceptibility changes varied by both genetic background and sex. Galbut virus overall has minimal influences on host transcriptional responses, consistent with minimal phenotypic impacts of galbut virus infection. Major constituents of the microbiome were not perturbed by galbut virus infection. All fitness measurements alterations attributable to galbut virus were small, but they were dependent by strain and sex, highlighting the importance of these variables in phenotype outcomes. However, these altered measurements in galbut virus infected flies were dwarfed in comparison to those measurements attributable solely by fly strain and sex. These findings further support a trend of predominately cryptic phenotypes of partitivirus infections. To understand how the virome interacts with other microbial constituents, we specifically searched for polymicrobial interactions within the field of vector-borne diseases. I. scapularis ticks harbor a variety of microorganisms, including eukaryotes, bacteria and viruses. Some of these can be transmitted to and cause disease in humans and other vertebrates. Others are not pathogenic but may impact the ability of the tick to harbor and transmit pathogens. A growing number of studies have examined the influence of bacteria on tick vector competence but the influence of the tick virome remains less clear, despite a surge in the discovery of tick-associated viruses. In this study, we performed shotgun RNA sequencing on 112 individual adult I. scapularis collected in Wisconsin, USA. We characterized the abundance, prevalence and co-infection rates of viruses, bacteria and eukaryotic microorganisms. We identified pairs of tick-infecting microorganisms whose observed co-infection rates were higher or lower than would be expected, or whose RNA levels were positively correlated in co-infected ticks. Many of these co-occurrence and correlation relationships involved two bunyaviruses, South Bay virus and blacklegged tick phlebovirus-1. These viruses were also the most prevalent microorganisms in the ticks we sampled and had the highest average RNA levels. Evidence of associations between microbes included a positive correlation between RNA levels of South Bay virus and Borrelia burgdorferi, the Lyme disease agent. These findings contribute to the rationale for experimental studies on the impact of viruses on tick biology and vector competence. Follow-up analyses on a second population of I. scapularis ticks derived from New York, USA revealed that these potential functional relationships may be population-specific. When evaluating South Bay virus, blacklegged tick phlebovirus-1, and B. burgdorferi in these individual ticks, no correlative or cooccurrence associations were observed. The lack of concordance between populations suggests that interactions between microbial constituents may be fluid, and change based upon location and populations. To characterize the biology of tick-associated viruses, an attempt to isolate South Bay virus was performed. Despite using mammalian and tick cell lines, we were unsuccessful in isolating South Bay virus through in vitro cell culture. The lack of success accents the challenge for understanding the biology of these arthropod-specific viruses. Further additional attempts to acquire infectious South Bay virus, such as creating a reverse genetics system, are warranted for its biological characterization.
Keywords: Drosophila melanogaster; Ixodes scapularis; virome; galbut virus; Aedes aegypti; partitivirus